1985
DOI: 10.1128/aac.27.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Survey of plasmids and resistance factors in Campylobacter jejuni and Campylobacter coli

Abstract: A total of 688 isolates of Campylobacter jejuni and Campylobacter coli were screened for the presence of plasmid DNA by agarose gel electrophoresis and were tested for susceptibility to ampicillin, chloramphenicol, erythromycin, streptomycin, and tetracycline. Of the isolates examined, 32% were noted to harbor plasmid DNA, ranging in size from 2.0 to 162 kilobases. Only tetracycline resistance was noted to correlate with the presence of plasmids. Plasmids capable of transferring tetracycline resistance via con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
63
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 23 publications
9
63
0
Order By: Relevance
“…None of the plasmids showed homology to any of the four classes of determinant from Enterobacteriaceae (11). These findings were subsequently confirmed by others (2,13 (4) by replicaplating 300 colonies onto Mueller-Hinton agar (Oxoid Ltd., London, England) with and without tetracycline (8 ,ug/ml).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…None of the plasmids showed homology to any of the four classes of determinant from Enterobacteriaceae (11). These findings were subsequently confirmed by others (2,13 (4) by replicaplating 300 colonies onto Mueller-Hinton agar (Oxoid Ltd., London, England) with and without tetracycline (8 ,ug/ml).…”
supporting
confidence: 71%
“…No plasmid-free derivatives were isolated spontaneously, but after exposure to 5 ,ug of ethidium bromide per ml, three plasmid-free derivatives were isolated from 1,500 colonies plated. Previous studies had indicated which restriction enzymes were likely to be useful for restriction mapping of C. jejuni plasmids (11,13). Plasmid DNA from pUA466 and its tetracycline-susceptible derivative, pUA649, were digested with AccI, AvaI, AvaII, BclI, HincII, PstI, XhoI, and XbaI (Boehringer Mannheim Canada, Ltd., Dorval, Quebec, or New England Nuclear Corp., Boston, Mass.)…”
mentioning
confidence: 99%
“…but not to Escherichia coli (53)(54)(55)(56)(57)(58)60). Despite the importance of plasmids to virulence in numerous other pathogens, it is generally believed that plasmids play no role in Campylobacter pathogenicity.…”
mentioning
confidence: 99%
“…2 (27,29) or the three streptococcal tet determinants (28) Two inverted repeats, potentially associated with the termination of transcription, were located downstream from the termination codon of tetOs (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…tetM was most often nonplasmid-mediated in the strains examined by Burdett et al (3). Tobian is usually plasmid mediated (27,29). Taylor et al (27) and Tenover et al (29) showed that Tcr plasmids from campylobacters do not hybridize to any of the tet determinants described by Levy and co-workers (15,21).…”
mentioning
confidence: 99%